Electronis Discussion

0 votes

In general, for a quaratic equation $ax^{2}+bx+c=0$ , sum of roots is defined as : $\frac{-b}{a}$ and product of roots is defined as : $\frac{-c}{a}$

$\therefore$ Here both the roots are $\beta$.

So, according to the given quadratic equation , we have $2\beta=\frac{b}{a}$ ---(1) and $\beta^{2}=\frac{c}{a}$-----(2)

Multiplying equations (1) and (2) and simplifying, we get $\beta^{3}=\frac{bc}{2a^{2}}$

Option C is correct

$\therefore$ Here both the roots are $\beta$.

So, according to the given quadratic equation , we have $2\beta=\frac{b}{a}$ ---(1) and $\beta^{2}=\frac{c}{a}$-----(2)

Multiplying equations (1) and (2) and simplifying, we get $\beta^{3}=\frac{bc}{2a^{2}}$

Option C is correct

1,109 questions

59 answers

8 comments

43,378 users